2021
DOI: 10.5194/ms-12-625-2021
|View full text |Cite
|
Sign up to set email alerts
|

Research on forming technology of rotary forging with double symmetry rolls of large diameter : thickness ratio discs

Abstract: Abstract. Rotary forging with double symmetry rolls (DSRs) is a new metal plastic forming technology developed on the basis of conventional rotary forging with a single roll, which uses a pair of symmetrical cone rolls to realize continuous local pressure plastic deformation of the workpiece. Large-diameter, thin discs are a key component in nuclear power, aerospace, deep-sea exploration, and other fields. At present, the forming process of large-diameter discs mainly includes welding and multiple local upsett… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 27 publications
0
0
0
Order By: Relevance
“…The new forging technology involves the use of a blank in the form of a cast blank. Based on the studies conducted, it was found that the use of cast blanks reduces material waste by about 80% with respect to the tech nology of [29] forging from a bar and re duces the energy consumption of the process by about 75%. Both options provide for ging with the intended shape and dimensions, although forging from a workpiece with a lower deg ree of deformation seems to be a safer option in terms of the possibility of breaking the material, as confirmed by the values of the Cockcroft-Latham criteria.…”
Section: Analysis Of the Current State Of Blacksmith Production In Th...mentioning
confidence: 99%
See 1 more Smart Citation
“…The new forging technology involves the use of a blank in the form of a cast blank. Based on the studies conducted, it was found that the use of cast blanks reduces material waste by about 80% with respect to the tech nology of [29] forging from a bar and re duces the energy consumption of the process by about 75%. Both options provide for ging with the intended shape and dimensions, although forging from a workpiece with a lower deg ree of deformation seems to be a safer option in terms of the possibility of breaking the material, as confirmed by the values of the Cockcroft-Latham criteria.…”
Section: Analysis Of the Current State Of Blacksmith Production In Th...mentioning
confidence: 99%
“…In addition to the types of forging with translational movement of the instrument, the methods of rotary forging were further developed. In particular, one of the latest deformation technologies is rotary for ging with double symmetry rolls (DSR) [27][28][29], developed on the basis of conventional rotary forging with double symmetry rolls, which uses a pair of symmetrical conical rolls to perform continuous local plastic deformation of the workpiece under pressure (Figs. 2 and 3).…”
Section: Analysis Of the Current State Of Blacksmith Production In Th...mentioning
confidence: 99%